1988
DOI: 10.1017/s0003356100037016
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of silage-based and dried forage-based diets for finishing beef cattle

Abstract: 1988). A comparison of silage-based and dried forage-based diets for nishing beef cattle. ABSTRACT Two experiments have been carried out to compare silage-based and dried forage-based diets for finishing beef cattle, and to examine the effect of supplementing the silage-based diet with additional protein. The three diets used in experiment 1 consisted of (1) grass silage supplemented with a lowprotein, cereal-based concentrate (98 g crude protein (CP) per kg dry matter (DM)) (2) grass silage supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
6
11
1
Order By: Relevance
“…Consistently, with the present meta-analysis, Steen (1996) reported that there was a tendency for steers given concentrates containing SBM to produce fatter carcasses than those given barley alone. In addition, Steen (1988b) and Moore (1988 and found that increasing protein intake tended to increase carcass fatness, although the effects only reached significance when the combined results of a series of experiments were analysed together (Steen, 1988a). Lowman et al (1985) reported that supplementation of grass silage with a mixture of barley and FM rather than with barley alone reduced the lean content of the forerib joint of steers by 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, with the present meta-analysis, Steen (1996) reported that there was a tendency for steers given concentrates containing SBM to produce fatter carcasses than those given barley alone. In addition, Steen (1988b) and Moore (1988 and found that increasing protein intake tended to increase carcass fatness, although the effects only reached significance when the combined results of a series of experiments were analysed together (Steen, 1988a). Lowman et al (1985) reported that supplementation of grass silage with a mixture of barley and FM rather than with barley alone reduced the lean content of the forerib joint of steers by 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with the present meta-analysis, Huuskonen et al (2014) observed that increased dietary CP concentration increased carcass fat score of growing cattle. Also Steen (1988b) and Moore (1988 and1989) found that increasing protein intake tended to increase carcass fatness, although the effects only reached significance when the combined results of a series of experiments were analysed together (Steen 1988a). Information on the reasons for increased fat deposition with increased protein intake is limited.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Steen 1996a, Huuskonen et al 2008, Huuskonen 2009a), but there is evidence that finishing cattle may respond to supplementary protein in barleybased concentrates when the grass silage digestibility is moderate or low (Waterhouse et al 1985) and in situations where the animals have very high growth potential (Steen 1996b). In some studies, excess protein supplementation has increased carcass fat classification (Steen and Moore 1988, 1989, Steen 1996a) but Berge et al (1993) reported that steers which were given protein supplementation had leaner carcasses than steers not given protein supplementation. Meat tenderness is the most important property of beef meat for consumers and it has been studied widely (e.g.…”
Section: Key-wordsmentioning
confidence: 99%